Trinity and Martin Luther. - Helmer, Christine (Lexham Press, 2017)
Annotation Martin Luther was classically orthodox.Scholars often portray Luther as a heroic revolutionary, totally unlike his peers and forebears--as if he alone inaugurated modernity. But is this accurate? Is this even fair? At times this revolutionary model of Luther has come to some shocking conclusions, particularly concerning the doctrine of the Trinity. Some have called Luther modalist or tritheist--somehow theologically heterodox.In The Trinity and Martin LutherChristine Helmer uncovers Luther's trinitarian theology. The Trinity is the central doctrine of the Christian faith. It's not enough for dusty, ivory tower academics to know and understand it. Common people need the Trinity, too. Doctrine matters.Martin Luther knew this. But how did he communicate the doctrine of the Trinity to lay and learned listeners? And how does his trinitarian teaching relate to the medieval Christian theological and philosophical tradition?Helmer upends stereotypes of Luther's doctrine of the Trinity.This definitive work has been updated with a new foreword and with fresh translations of Luther's Latin and German texts.
The Holy Spirit: Conclusion -- The Inner and Outer Trinity -- The Cross as the Eternal Sermon of the Father -- The Sites of Mutual Revelation -- The Hidden God (Deus Absconditus) in the Narrative of Trinitarian Revelation -- The Inner and Outer Trinity: Conclusion -- The Glorification of the Triune God in Creation -- The Trinitarian Structure of Revelation in Creation -- Doxology as Eschatological Impulse -- Conclusion -- Chapter 5: Conclusion -- Bibliography -- Names Index -- Scripture Index -- Old Testament -- New Testament.
Print version record.
Added to collection customer.56279.3
Keywords: Luther, Martin, -- 1483-1546.; Luther, Martin, -- 1483-1546.; Trinity -- History of doctrines; Trinity -- History of doctrines -- 16th century; Trinity -- History of doctrines; 1500-1599; Electronic books